Factions, Local Accountability, and Long-Term Development : County-Level Evidence from a Chinese Province - Fang, Hanming (World Bank, Washington, DC, 2019)
This paper investigates, both theoretically and empirically, the role of factional competition and local accountability in explaining the enormous but puzzling county-level variations in development performance in Fujian province of China. When the Communist armies took over Fujian from the Nationalist control circa 1949, Communist cadres from two different army factions were assigned as county leaders. For decades the Fujian Provincial Standing Committee of the Communist Party had been dominated by members from one particular faction, which we refer as the strong faction. Counties also differed in whether there was local guerrilla presence prior to the Communist takeover. The model predicts that county leaders from the strong faction were less likely to pursue policies friendly to local development, because their political survival relied more on their loyalty to the provincial leader than on the grassroots support from local residents. In contrast, the political survival of county leaders from the weak faction was based more on local grassroots support, which could be best secured if these leaders focused on local development. In addition, the local guerrilla presence in the county further improved the development performance either because it intensified local accountability of the county leader, or because it better facilitated the provision of local public goods beneficial to development. The paper finds consistent and robust evidence supporting these assumptions; being affiliated with weak factions and having local accountability are both associated with sizable long-term benefits in terms of growth, education, private-sector development, and survival in the Great Famine. The paper also finds that being affiliated with the strong faction and adopting pro-local policies are associated with higher likelihood of political survival. The empirical findings here suggest that factional competition contributes to efficiency in non-democratic countries, and that local accountability is a key ingredient for balanced development.